"Partial oxidation of methane and methanol on FeOx-, MoOx- and FeMoOx -SiO2 catalysts prepared by sol-gel method: a comparative study" (2020)
FeOx-, MoOx and FeMoOx-SiO2 materials prepared by a sol-gel procedure have been evaluated as catalysts for the partial oxidation of methane and methanol. The effect of decreasing the pH of the synthesis gel on the chemical nature of FeOx and MoOx species has been investigated. Characterization results show that low pH improves the dispersion of metal oxide species present in SiO2 matrix. For FeOx/SiO2 materials, the presence of dispersed FeOx species (rather than bulk Fe2O3) improves the selectivity to formaldehyde in the partial oxidation of methane and methanol. For FeMoOx/SiOx catalysts, dispersed species favor the selectivity to formaldehyde only for methane oxidation. In contrast, for bimetallic FeMoOx/SiOx system, a better dispersion does not improve the selectivity to the aldehyde in methanol oxidation. In spite of the fact that the activation temperature for methane oxidation is remarkably higher than that for methanol oxidation, catalytic results show that the most active and selective catalysts for the partial oxidation of methane are also the most effective materials for the partial oxidation of methanol.